2016
DOI: 10.1002/jbm.a.35864
|View full text |Cite
|
Sign up to set email alerts
|

Isolated effect of material stiffness on valvular interstitial cell differentiation

Abstract: Previous methods for investigating material stiffness on cell behavior have focused on the use of substrates with limited ranges of stiffness and/or fluctuating surface chemistries. Using the co-polymer system of n-octyl methacrylate crosslinked with diethylene glycol dimethacrylate (DEGDMA/nOM), we developed a new cell culture platform to analyze the isolated effects of stiffness independent from changes in surface chemistry. Materials ranging from 25 kPa to 4,700 kPa were fabricated. Surface analysis includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
(195 reference statements)
0
6
0
Order By: Relevance
“…Calcification is a main factor reported to occur with long use of implants and consequently cause failure. Calcific degeneration remains a major obstacle facing the translation of tissue‐engineered vascular grafts for arterial repair . Thus, calcification degree is an important indicator to evaluate the success of the implanted material.…”
Section: Discussionmentioning
confidence: 99%
“…Calcification is a main factor reported to occur with long use of implants and consequently cause failure. Calcific degeneration remains a major obstacle facing the translation of tissue‐engineered vascular grafts for arterial repair . Thus, calcification degree is an important indicator to evaluate the success of the implanted material.…”
Section: Discussionmentioning
confidence: 99%
“…A collagen gel is reminiscent of ECM conditions in that collagen is one of the representative proteins existent in vivo . However, some synthetic polymers like a co-polymer system of n-octyl methacrylate crosslinked with diethylene glycol dimethacrylate (DEGDMA/nOM) prove ideal for differentiation studies looking for independent effects of substrate stiffness without the inconsistency of surface chemistry [94]. This co-polymer system elucidated the mechanosensitivity of cells to their substrates by revealing that after a certain stiffness threshold, gene expression does not increase but rather re-organizes corresponding to the formation of osteoblastic markers which are known to associate with higher stiffness.…”
Section: Biophysical Regulation Of Cell Reprogrammingmentioning
confidence: 99%
“…Overall, no matter the amount of mechanical loading, hMSCs will lose their stemness and gain the factors towards osteoblastic or tendon/ligament differentiation [98, 101]. The cell orientation will convert to a direction perpendicular to stress orientation, providing a tissue response that seeks to balance the stress it is exposed to [94]. For example, a recent study developed a probe to investigate cell actin stress and its role in cell reprogramming and differentiation, which could elucidate how cellular mechanics can influence cell fate [103].…”
Section: Biophysical Regulation Of Cell Reprogrammingmentioning
confidence: 99%
“…The phenotype of valvular interstitial cells (VICs), the most abundant and plastic cell population in the valve, can be modulated by the properties of cell culture substrate/matrix . It has been revealed that matrix stiffness affects the activation and osteogenic differentiation of VICs . Moreover, the morphology and architecture of valvular ECM have been shown to instruct the attachment and spreading of VICs .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 It has been revealed that matrix stiffness affects the activation and osteogenic differentiation of VICs. [8][9][10] Moreover, the morphology and architecture of valvular ECM have been shown to instruct the attachment and spreading of VICs. 11,12 Several studies have performed uniaxial tensile testing on tissue-engineered scaffolds, 13,14 but uniaxial testing is insufficient to fully characterize the scaffold mechanical properties as it fails to capture the complex cross-coupling (stress along one axis is affected by the strain level along the perpendicular axis) experienced by the anisotropic tissues.…”
mentioning
confidence: 99%